Morphometric analysis of the main river systems at Ulu Muda Forest Reserve, Kedah, Peninsular Malaysia - Miniandi, Nirwani Devi; Sulaiman, Mohd Sofiyan; Zakaria, Razak; Mohd Razali, Sheriza; Jamil, Nor Rohaizah (Malaysian Nature Society, 2021)
An attempt was made to quantify the catchment characteristics of two main rivers that drain into Muda dam. The dam and its associated reservoir form part of Ulu Muda Forest Reserve (UMFR) located in Kedah, Peninsular Malaysia. UMFR is very important as the last great piece of rainforest in the northern part of the peninsula. We used a Geographical Information System (GIS) for catchment delineation, morphometric analysis and extracting various catchment parameters. The results provide the basis for the abstraction of the shape and hydrological processes within UMFR. The structure of the catchments inferred from the study includes stream order, shape, steepness, degree of stream branching, dissection and watershed elongation. Sungai Muda and Sungai Teliang catchments can be classified as dendritic; the whole area has uniform underlying lithology, and geologically there has been no probable uplift in the basin based on the analysis of stream number. The low value of mean bifurcation ratio (Rb) in Muda Catchment indicates the shape of the catchment is more nearly circular while in Teliang catchment the shape is more elongated (high mean Rb), with implications for flow rate, travel time and flood regimes. The results should be useful for proper understanding of the variety, form and hydrological processes of the catchment in terms of development, management and conservation planning.